Critical thinking in the teaching of the ukrainian language as a foreign. - Grossu, Nataliia; Гроссу, Наталія Валентинівна (Рівне : РДГУ, 2020)
The article is devoted to the current issue of the development of critical thinking technology. Innovative technologies for the development of critical thinking consisting in the practical implementation of the person-oriented approach in training are considered. The methods of forming critical thinking, which contribute to the formation of foreign language communicative competence, are considered too. The author reveals practical ideas of the development of critical thinking in the students of the preparatory faculty of the university in the process of teaching Ukrainian as a foreign language. Examples of the use of technology through reading and writing are given: during the study of the general literary Ukrainian language (the first semester) and the course “Country Studies” (discipline “Ukrainian as a foreign language”) (the second semester). The possibilities of developing critical thinking in the process of project implementation were presented. Examples of the implementation of pedagogical technology for the development of critical thinking during classes are presented. The author substantiates the possibility and necessity of using the technology of critical thinking in teaching Ukrainian as a foreign language at the initial stage of its study. It is noted that the most effective form of teaching critical thinking is the implementation of group work, because it promotes the development of independence, curiosity, the ability to make independent assessments, argue their opinions, prove or disprove their decision. The study made it possible to conclude that the technology of critical thinking development, creating a motivating favorable environment in the class, maximally adapt the learning process to the individual characteristics of foreign students. Стаття присвячена актуальній на сьогоднішній день проблемі розвитку технології критичного мислення (critical thinking). Розглядаються інноваційні технології розвитку критичного мислення, що складаються з практичної реалізації особистісно-орієнтованого підходу в навчанні. Розглянуті методи формування критичного мислення, які сприяють формуванню іншомовної комунікативної компетенції. Автор висвітлює ідеї розвитку критичного мислення у слухачів підготовчого відділення університету під час викладання української мови як іноземної. Наведено приклади використання технології через читання та письмо: під час вивчення загальнолітературної української мови (перший семестр) та курсу «Країнознавство» (дисципліна «Українська мова як іноземна» (другий семестр). Розкриваються можливості розвитку критичного мислення у процесі виконання проєктів. Наведено приклади застосування педагогічної технології розвитку критичного мислення під час аудиторних занять. Автор обґрунтовує можливість і необхідність застосування технології критичного мислення у викладанні української мови як іноземної на початковому етапі її вивчення. Доведено, що найефективніше навчання критичного мислення здійснюється в процесі використання групової форми роботи, оскільки вона сприяє розвитку самостійності, допитливості, уміння здійснювати незалежну оцінку, приводити аргументацію своїх думок, доведити або спростувати своє рішення. Проведене дослідження дало автору підстави дійти такого висновку: технології розвитку критичного мислення, створюючи мотивуюче сприятливе середовище в процесі заняття, максимально адаптують процес навчання до індивідуальних особливостей студентів-іноземців.
Критичне мислення у викладанні української мови як іноземної
Keywords: critical thinking; educational syncvein; Ukrainian language; foreign students; project method; memory cards; критичне мислення; навчальний сінквейн; карти пам'яті; метод проєктів; українська мова